2019
DOI: 10.1177/1687814018824916
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of the relationship between driving skills and driving behaviors among Chinese bus drivers

Abstract: To provide helpful suggestions to bus companies regarding reducing the number of bus accidents and improving public transportation safety, we further researched the relationship between driving skills and driving behaviors; bus drivers from six bus companies of the Hefei Bus Group were investigated. The reliability and validity of the Driver Behaviour Questionnaire, the Driver Skill Inventory, and 287 valid questionnaires were tested; the relationships between the Driver Behaviour Questionnaire and Driver Skil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 33 publications
1
10
0
Order By: Relevance
“…Conversely, younger male drivers who have lower education level and less experience were found to exhibit risky behavior, affecting the safety of the trip [48,51]. Bus safety is associated with drivers who exhibit less sensation-seek and high self-reporting features [53]. Another study confirmed a significant correlation between driver experience and safer bus trips [61].…”
Section: ) Vehicle Design and Driver Experiencementioning
confidence: 96%
See 4 more Smart Citations
“…Conversely, younger male drivers who have lower education level and less experience were found to exhibit risky behavior, affecting the safety of the trip [48,51]. Bus safety is associated with drivers who exhibit less sensation-seek and high self-reporting features [53]. Another study confirmed a significant correlation between driver experience and safer bus trips [61].…”
Section: ) Vehicle Design and Driver Experiencementioning
confidence: 96%
“…The study focused on the experience of driver as a main factor and demonstrated that drivers with no experience are likely to be involved in accidents, violations, and lapses. Similarly, using DBQ, a survey on driving behavior was conducted among bus drivers in Hefei, China [53]. The study showed a significant correlation between the experience of driver and safe bus trips.…”
Section: 4) Experiencementioning
confidence: 99%
See 3 more Smart Citations